Extreme small bowel resection in malrotation with acute midgut volvulus in a 3-year old boy: a case report: Obsežna resekcija tankega črevesa pri malrotaciji z akutnim volvulusom pri tri letnem dečku: prikaz primera - Ivanecz, Arpad; Roškar, Zdravko; Potrč, Stojan (Acta Medico-Biotechnica, 2021)
Purpose: Malrotation with midgut volvulus is a rare congenital anomaly that generally presents acutely in the neonatal period, with bilious vomiting, and requires surgical intervention. It is rarely observed beyond the first year of life, when the diagnosis can be difficult because of intermittent symptoms and vague clinical findings, which can subsequently delay appropriate treatment. Chronic volvulus associated with malrotation has the potential to turn into acute vascular congestion and arterial insufficiency secondary to torsion of the superior mesenteric vessels. Early diagnosis and surgical treatment are essential to prevent progression to transmural bowel infarction.Case report: We present the case of a 3-year-old boy with a 1-year history of recurrent abdominal pain and intermittent vomiting, which was evaluated many times at other institutions without a definitive diagnosis. Finally, the boy was referred as an emergency, with signs of an acute abdomen and septic shock. Upon urgent laparotomy, midgut volvulus caused by malrotation with extensive intestinal necrosis was found, which necessitated an extreme resection of the small bowel. The postoperative course was uneventful, and presently, 1 year after the operation, the boy is on total parenteral nutrition, thrives normally, eats regular food, and has no diarrhea or signs of liver failure. Although there is some impairment in his quality of life, he can practice almost completely normal daily activities for a child of his age.Conclusion: In this article, we discuss the diagnostic pitfalls that can occur when symptoms of midgut malrotation develop beyond the neonatal period, the difficulties of management in an emergency setting, and therapeutic options for the patient after massive small bowel resection.
Keywords: Malrotation; midgut volvulus; child; emergency; short bowel syndrome